INVESTIGATING PAST TENSE ON TWILIGHT NOVEL BY STEPHANIE MEYER - Vina Anis Azizah (Faculty of Education and Teachers Training, 2021)
The novel is one of the literary works that are very popular in a whole society. For understanding novels, it is necessary to read the types of tense carefully. The researcher will analyze the past tense that appears in this novel. Past tense explains the events that occur in the past story that the character has experienced. Past tense is a word that indicates something that happened in the past. The word that often appears, for example, was yesterday, last week, and many others. In the novels, past tenses function as a marker of activities that occurred in the past. This research focuses on the dialogue contained in the novel. The use of past tense sentences is influential and shows when something happened so readers who use English as EFL can understand and apply. The purpose of this research is to analyze the past tense formula and the function.